Reliability, Validity, and Sensitivity to Change of the Cochin Hand Functional Disability Scale and Testing the New 6-Item Cochin Hand Functional Disability Scale in Systemic Sclerosis. Issue 3 (April 2021) - Gheorghiu, Ana Maria; Gyorfi, Hermina; Capotă, Răzvan; Matei, Alexandru; Oneaţă, Raida; Bojincă, Mihai; Stoica, Victor; Mihai, Carina
Abstract : N/A: Systemic sclerosis (SSc) is a chronic autoimmune disease causing complex hand disability. A reliable tool for hand function assessment in SSc is the Cochin Hand Functional Disability Scale (CHFS). More recently, a short-form CHFS of 6 items (CHFS-6) has been developed. Objectives: To validate the CHFS and the new CHFS-6 in Romanian patients with SSc. Patients and Methods: Consecutive patients with SSc who completed the CHFS were included. All patients were assessed according to the recommendations of the European Scleroderma and Research Trials and also completed the Scleroderma Health Assessment Questionnaire and the Hand Mobility in Scleroderma questionnaire. Finger range-of-motion distances were measured. Results: Seventy patients, 63 female and 7 male patients (age median, 53.0 years; interquartile range [IQR], 21.0 years), were included. Twenty seven had diffuse cutaneous involvement (dcSSc). Median CHFS and CHFS-6 at baseline were 25.0 (IQR, 37.0) and 8.0 (IQR, 13.0), respectively. The internal consistency (Cronbach α = 0.96, respectively, 0.90, in all 70 patients) and test-retest reliability (intraclass correlation coefficient = 0.98 for both, in 38 patients) of both CHFS and CHFS-6 were excellent. The CHFS-6 had a very high correlation with the CHFS. There were moderate to good correlations with Hand Mobility in Scleroderma, Scleroderma Health Assessment Questionnaire, and the anthropometric measurements (construct validity). In patients with early dcSSc with a second evaluation, we found good to moderate sensitivity to change (standardized response mean of 0.8 and effect size of 0.4 for CHFS, and standardized response mean of 1.1 and effect size of 0.6 for CHFS-6). Conclusions: The CHFS and CHFS-6 are valid and easy-to-use tools for hand involvement in SSc, which can be used in clinical or research setting. Abstract : Supplemental digital content is available in the text.